The ABCT31 Transporter Regulates the Export System of Phenylacetic Acid as a Side-Chain Precursor of Penicillin G in Monascus ruber M7 - Ramzan, Rabia; Virk, Muhammad Safiullah; Chen, Fusheng (Frontiers in Microbiology, 2022)
The production of β-lactams is compartmentalized, the transportation of end product and its precursors require to traverse membrane barriers. Phenylacetic acid-CoA ligase is the enzyme which stimulate the side chain activation of precursor of phenylacetic acid (PAA) by CoA. Whereas the PAA transportation system is unclear yet, so the engagement of transmembrane transporter proteins can only be postulated. To discover ABC transporters involved in the activation of the side chain of PAA precursor, examination of the expression level of 38 ABC transporters checked in M. ruber's genome, culturing with and without PAA. When cells are cultivated or exposed to significant doses of PAA, Abct31 is considerably upregulated. The gene deletion (Δabct31) has been used to find out the role of the abct31 gene as a transporter. The feeding of PG pathway precursor side chains and amino acids, such as D-valine, L-cysteine and phenylacetic, and, was done to determine the involvement of the Δabct31 gene as a phenylacetic acid transporter. The findings indicated that feeding D-valine, L-cysteine, and phenylacetic acid had a substantial impact on the morphologies and production of secondary metabolites (SMs) of Δabct31 strain including M. ruber M7. Consequently, the sensitivity to weak acids and PAA was significantly increased. The findings of UPLC-MS/MS analysis demonstrated that Δabct31 did not interrupt the synthesis of PG in M. ruber M7. According to the results it could be determined that Δabct31 is involved in resistance and detoxification of the weak acids including the phenylacetic acid in M. ruber M7.